2017
DOI: 10.1016/j.surfcoat.2016.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Gas and liquid-fuelled HVOF spraying of Ni50Cr coating: Microstructure and high temperature oxidation

Abstract: Ni50Cr thermally sprayed coatings are widely used for high temperature oxidation and corrosion in thermal power plants. In this study, a commercially available gas atomised Ni50Cr powder was sprayed onto a power plant alloy (ASME P92) using both gas and liquid fuelled high velocity oxy-fuel (HVOF) thermal spray. Microstructures of the two coatings were examined using SEM-EDX, XRD, oxygen content analysis and mercury intrusion porosimeter. The gas fuelled coating had higher levels of oxygen content and porosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The XRD patterns of the as-sprayed coatings (Fig. 3) showed that the Ni peaks shifted towards shorter lattice parameters (higher 2θ angles) which might be due to the level of residual stresses within the coatings (macrostrain) [15]. The peak broadening of the as-sprayed coatings compared to the powders is due to three primary factors of a) presence of micro-strain due to the plastic deformation during the HVAF spraying process [29], b) reduction in crystallite size, and c) instrumental broadening due to beam size, sample to detector distance, air scatter, etc.…”
Section: Microstructure Of As-sprayed Coatingsmentioning
confidence: 99%
“…The XRD patterns of the as-sprayed coatings (Fig. 3) showed that the Ni peaks shifted towards shorter lattice parameters (higher 2θ angles) which might be due to the level of residual stresses within the coatings (macrostrain) [15]. The peak broadening of the as-sprayed coatings compared to the powders is due to three primary factors of a) presence of micro-strain due to the plastic deformation during the HVAF spraying process [29], b) reduction in crystallite size, and c) instrumental broadening due to beam size, sample to detector distance, air scatter, etc.…”
Section: Microstructure Of As-sprayed Coatingsmentioning
confidence: 99%
“…The microstructure of the coating is typical of the HVOF dense metallic coating with a low degree of porosity. HVOF thermal spraying using a liquid fuel tends to result in a relatively low amount of oxides in the coatings than in gas fuel HVOF [22]. Indeed, no oxides were detected by PXRD on the coating surface (not shown here).…”
Section: As-deposited Microstructurementioning
confidence: 76%
“…The method gives promising results regarding allowing the formation of suspension spraying layer [93][94][95]. By introducing the axial powder injection, the new high-velocity suspension lame spraying (HVSFS) process typically would be able to resolve the injection complications [96][97][98].…”
Section: High-velocity Suspension Plasma-sprayingmentioning
confidence: 99%